Effects of environmental factors on corporate strategy and performance of manufacturing industries in Indonesia - Rachmad Hidayat (Journal of Industrial Engineering and Management, 2015)
Purpose: The purpose of this study was to examine and obtain empirical evidence of the effects of external and internal environmental factors on the strategy and performance of manufacturing companies. Design/methodology/approach: This study used primary data obtained by distributing questionnaires to 150 respondents of manufacturing companies in Indonesia spreading over six major cities in Java such as Jakarta, Banten, Bandung, Yogyakarta, Semarang and Surabaya. Samples were taken by using the systematic random sampling technique. The technique was used since those major cities had different numbers of manufacturing companies. Subsequently, the feasibility of the model was tested. Several indices of model feasibility would be used to test the model developed in this structural equation model. In case of a sub-optimal model, a model modification was to be performed by adding or removing paths so that the chi-square values would decrease by the values of the index. Findings and Originality/value: Results showed that internal and external environmental factors, through the operating environments and the remote environments of manufacturing industries, jointly affected the companies’ understanding of the condition of the industrial environments to establish strategic goals in order to achieve optimal performance of manufacturing industry. Practical implications: The internal and external environmental factors through the operating and remote environments had effects on the strategy of manufacturing companies in Indonesia. However, both internal and external environments did not affect the performance of manufacturing companies in Indonesia. There was a tendency that manufacturing companies were to observe the occurring macro-economic conditions. Manufacturing industries were faced with the pressures from competition, customers and suppliers that affected companies’ revenue. Performance of manufacturing industries was more influenced by macro-economic conditions that have not recovered from the global crisis. Originality/value: This study was conducted to determine the effects of environmental factors on the corporate strategy and performance. The effects of the industrial environments are crucial since the more complicated changes in the industrial environments the greater the impacts it has on the resources, structures and processes in the company. Environmental factors of the industry present both organizational strengths and weaknesses, which would affect the strategy and performance of the industry.